2010
DOI: 10.1038/cgt.2009.89
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of bioluminescence imaging to follow siRNA or chemotherapeutic treatments in osteosarcoma preclinical models

Abstract: Osteosarcoma is the most common malignant primary bone tumor for which pertinent preclinical models are still needed to develop new therapeutic strategies. As osteosarcoma growth is strongly supported by bone resorption, previous studies have inhibited the cytokine receptor activator of nuclear factor-kB ligand using antibodies or recombinant proteins. However, its expression has not yet been inhibited using genetic approaches using small interfering RNA. To optimize the delivery of small interfering RNA to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 36 publications
(47 reference statements)
1
32
0
Order By: Relevance
“…27 Using these plasmids, lentiviral particles were produced to stably transduce HEK 293 cells. We selected two modified HEK 293 cell lines that express similar levels of the recombinant LucF transcript associated with either WT or Mut exon 23 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Using these plasmids, lentiviral particles were produced to stably transduce HEK 293 cells. We selected two modified HEK 293 cell lines that express similar levels of the recombinant LucF transcript associated with either WT or Mut exon 23 (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…For LacZ-and Mut-shRNAs synthesis, sequences of corresponding siRNAs were used to design 2 oligonucleotides (Eurogentec) with an overlapping sequence as described by Chang et al Oligonucleotide duplexes (sequences in Figure 1a, Sigma, Saint-Quentin Fallavier, France) corresponding to 54 base pairs of the WT or the Mut Brtl Col1a1 exon 23 sequence were cloned at the MluI site in the 3' untranslated region of the firefly luciferase gene (LucF) in the pLNT-LucF plasmid. 27 Using the ViraPower Lentiviral Expression System (Invitrogen, Saint Aubin, France), the resulting plasmids were used for lentiviral particles production. To measure lentiviral titration and transduction efficiency, EGFP encoding particles were coproduced utilizing pFG12.…”
Section: Rnai Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Although aggressive surgical treatment of osteosarcoma is associated with improved survival, 13,20 there remains a need for further development of preclinical models to develop new therapeutic approaches. 16 We report the development of an orthotopic nude mouse model in which the human osteosarcoma cell line, Krib-1, was implanted directly into the VB. We demonstrate that the implanted mice subsequently experience a progressive neurological decline in a reproducible and predictable time frame correlating with increasing severity of spinal canal compression by pathological evaluation.…”
mentioning
confidence: 99%
“…[42,44] Preclinical experiments have already demonstrated that synthetic siRNAs are potent inhibitors of a variety of diseases in vivo, [43,45] including hypercholesterolaemia, [46][47] liver cirrhosis, [48][49][50] hepatitis B virus (HBV), [51][52][53][54] human papillomavirus, [53,55] ovarian cancer, [56][57] and bone cancer. [58][59][60] Since the therapeutic benefit of RNAi inevitably relies on the delivery of synthetic siRNA into cells, and its systemic delivery to target cells is complex, the development of efficient gene delivery systems represents a challenging hurdle in the field of gene therapy. [1,[61][62] …”
Section: Rna Interferencementioning
confidence: 99%